Flow-type landslide fragility of reinforced concrete framed buildings. (15th January 2017) - Parisi, Fulvio; Sabella, Giuseppe
Highlights: The fragility of low-rise RC buildings to flow-type landslides is investigated. A fragility analysis methodology was developed to assess landslide vulnerability. Best-fit probability distributions for landslide demand and capacity were obtained. Landslide fragility curves for both out-of-plane and in-plane damages were derived. The influence seismic design on landslide fragility was assessed. Abstract: Flow-type landslides may be triggered by several events such as heavy rainfalls, typically producing huge losses. Landslide risk may be rationally evaluated and mitigated with probabilistic approaches. In this paper, physical vulnerability of reinforced concrete buildings to flow-type landslides is assessed. Fragility analysis was carried out by assuming flow velocity as intensity measure, several damage states, and different mechanical models for beams, columns and masonry infill walls. Uncertainties in landslide impact loading, material properties, size and reinforcement of members, and capacity models were taken into account. Both earthquake-resistant and gravity-load designed framed buildings were assessed as being representatives of two building classes. Based on Monte Carlo simulation and a specific fragility analysis methodology, a set of landslide fragility curves were derived. Analysis results show that landslide fragility significantly depends on the presence and type of infill walls, which influences both out-of-plane and in-plane failure modes of walls themselves and RC frames. In addition, the proposed landslide fragility curves demonstrate that seismic design of RC buildings also plays a key role in the mitigation of their flow-type landslide fragility.